Perancangan Interior Galeri dan Diorama Soerabaja-Tempo Doeloe - Ester Rina Hendratno; Sriti Mayang Sari (Intra, 2014)
Surabaya City is one of big metropolitan city in Indonesia that known as Hero City because of its historical battle value at the past that give a big role to the independence of Indonesia. However, there are few places that can attract people to appreciate the struggle of the past generation that fought for Indonesia’s freedom. As the city grows, so many shopping centers built as recreation center and the impact is that historical recreation is not attractive for local people anymore. With designing a recreation place about Surabaya in past time by using diorama concept that show the old town of Surabaya in the colonial age and adapt people’s modern lifestyle nowadays, the designer hope that the people, especially in Surabaya City, will appreciate more and have a good knowledge about history of Surabaya City and be proud to our heroes in this city.